The Detection Of Malingered Levels Of Cognitive Impairment On The Nevada Brief Cognitive Assessment Instrument: Toward the Development of Rapid, Quantitative Measures of Feigned Low Intelligence - Wildman, Robert W. (Advances in Social Sciences Research Journal, 2018)
A methodology for detecting the downplaying of examinees’ cognitive abilities on the Nevada Brief Cognitive Assessment Instrument (NBCAI) is developed, described and validated.